Legal Protection of the Interests of Fair Competition in the Business Sector: Analysis of Anti-Trust and Cartel Violations - Inawati, Inawati; Rahmadi, Meiliyan; Mahmuctarom, Mahmuctarom (LifeSciFi, 2024)
Antitrust and cartel violations in the business sector reveal various fundamental problems that need to be addressed to realize healthier business competition, with a focus on low legal awareness among business actors, obstacles in law enforcement, challenges in regulatory oversight, and lack of regulatory effectiveness. This research aims to identify factors that hinder the effective implementation of antitrust and cartel laws in the business sector in Indonesia. This research uses a qualitative approach by conducting in-depth interviews with various related parties, including business actors, regulators, and legal experts. Data analysis was carried out using thematic techniques to identify patterns and main themes that emerged from the interviews. The research results show that low legal awareness among business actors is one of the main factors that exacerbate the problem of antitrust violations and cartels. In addition, law enforcement is hampered by limited human and financial resources, as well as regulatory oversight that is not yet effective in the regions, also making it difficult to achieve the goal of optimal legal protection. The implications of this research suggest the need to increase legal education, reform law enforcement, adapt more flexible regulations, and strengthen the supervisory system as strategic steps to increase compliance with business competition law to increase healthy business competition in Indonesia.